2017
DOI: 10.7150/thno.17846
|View full text |Cite
|
Sign up to set email alerts
|

Thermoacoustic Imaging and Therapy Guidance based on Ultra-short Pulsed Microwave Pumped Thermoelastic Effect Induced with Superparamagnetic Iron Oxide Nanoparticles

Abstract: Multifunctional nanoparticle-mediated imaging and therapeutic techniques are promising modalities for accurate localization and targeted treatment of cancer in clinical settings. Thermoacoustic (TA) imaging is highly sensitive to detect the distribution of water, ions or specific nanoprobes and provides excellent resolution, good contrast and superior tissue penetrability. TA therapy is a potential non-invasive approach for the treatment of deep-seated tumors. In this study, human serum albumin (HSA)-functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…The shockwaves produced by the thermal expansion can be acquired by an ultrasound transducer and reconstructed to form TA images. Wen and collaborators have recently studied human serum albumin (HSA) functionalized superparamagnetic iron oxide nanoparticles (HSA-SPIO) as a theranostic nanosystem with potential application for MRI, TA imaging, and treatment of tumors [ 196 ]. The authors intravenously injected HSA-SPIO in 4T1 tumor-bearing mice that were localized by MRI.…”
Section: Biomedical Applications Of Thermal-nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shockwaves produced by the thermal expansion can be acquired by an ultrasound transducer and reconstructed to form TA images. Wen and collaborators have recently studied human serum albumin (HSA) functionalized superparamagnetic iron oxide nanoparticles (HSA-SPIO) as a theranostic nanosystem with potential application for MRI, TA imaging, and treatment of tumors [ 196 ]. The authors intravenously injected HSA-SPIO in 4T1 tumor-bearing mice that were localized by MRI.…”
Section: Biomedical Applications Of Thermal-nanomaterialsmentioning
confidence: 99%
“…( c ) HSA-SPIO as a TA therapeutic agent for tumor therapy. Reproduced with permission from [ 196 ]. Copyright Ivyspring International Publisher, 2017.…”
Section: Figures Scheme and Tablementioning
confidence: 99%
“…[1][2][3] Therefore, it's still urgent to develop alternative cancer treatment modalities with high efficacy and low side effects. In recent years, innovative treatment approaches, such as microwave therapy, radiofrequency therapy, ultrasound therapy, and phototherapy have attracted increasing interest [4][5][6][7][8] Among them, phototherapy modalities have received the most attention owing to their high efficiency, spatial specificity, noninvasive or minimally invasive feature, and remote control capability. [9,10] In particular, photothermal therapy (PTT), which relies on converting light energy into heat via irradiation of photothermal agents (PTAs), is an attractive and non-invasive technique for treating cancers.…”
Section: Introductionmentioning
confidence: 99%
“…A possibility is to employ nanomaterials that, in synergy with MWs, improve the temperature absorbing energy [ 21 ] and may promote a Joule heating effect [ 92 ]. Additionally, it is reported that some nanotools, e.g., iron oxide NPs and carbon nanotubes, are able to produce shock waves under a MW input, provoking a mechanical stimulation of the cells [ 93 , 94 ]. The presence of these NPs moreover tunes both the thermal and electrical conductivities of the tissue, increasing the thermal ablation efficiency [ 95 ], but the operating mechanism is still unclear [ 96 ].…”
Section: Microwave Responding Npsmentioning
confidence: 99%